Updated review on soiling of solar photovoltaic systems Morocco and India contributions. (15th August 2021) - Laarabi, B.; El Baqqal, Y.; Rajasekar, N.; Barhdadi, A.
Abstract: Solar energy as abundant energy can easily be converted to electricity using the different solar energy technologies. However, the conversion efficiency is highly affected by many factors such soiling phenomenon. This refers to the accumulation of dust particles and other contaminants on the front surface of the system which prevent the sunlight from reaching the cells or the collectors. The present work is mainly focusing on understanding this phenomenon especially for photovoltaic modules. It represents an updated survey on soiling process and its methods of quantitation based on measuring deposited dust, transmittance or by evaluating the real response of the photovoltaic module. It includes as well the different factors influencing soiling, which have been categorized into five categories related to the module characteristics, the surrounding environment, the climatic conditions, the exposure conditions and the soiling properties. The different methods to mitigate its effect mainly natural, manual, mechanical and self-cleaning have been also discussed. It presents as well a summary of the key contributions on this phenomenon in both countries Morocco and India. This will be as a paved guide to help readers to better understand soiling phenomenon and also to get a clear idea about the trend of research in both countries Morocco and India. Highlights: Soiling process and the different steps of this phenomenon have been discussed. Methods of quantification of soiling have been summarized. In-depth investigation on the factors influencing soiling phenomenon. Summary of the various cleaning methods developed so far to mitigate soiling. A summary of all studies conducted on soiling in Morocco and India countries.